2021
DOI: 10.1186/s13613-021-00846-0
|View full text |Cite
|
Sign up to set email alerts
|

An international tool to measure perceived stressors in intensive care units: the PS-ICU scale

Abstract: Background The intensive care unit is increasingly recognized as a stressful environment for healthcare professionals. This context has an impact on the health of these professionals but also on the quality of their personal and professional life. However, there is currently no validated scale to measure specific stressors perceived by healthcare professionals in intensive care. The aim of this study was to construct and validate in three languages a perceived stressors scale more specific to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, as previously demonstrated that it is not the objective characteristics of a stressful situation (nature, severity, frequency) that influence the subject's ability to adapt to the situation, but rather the subjective evaluation that the subject cares, in other words how he perceives the situation. 18 Second, our questionnaire did not explore unit management, thus we cannot exclude the possibility that the respondents are selected and that our results are not extendable to all the units. Third, our study is limited at a single country (France) and only one medical discipline (intensivist), however, we deliberately started with a French survey because of the very different organizations of ICU exists in Europe.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, as previously demonstrated that it is not the objective characteristics of a stressful situation (nature, severity, frequency) that influence the subject's ability to adapt to the situation, but rather the subjective evaluation that the subject cares, in other words how he perceives the situation. 18 Second, our questionnaire did not explore unit management, thus we cannot exclude the possibility that the respondents are selected and that our results are not extendable to all the units. Third, our study is limited at a single country (France) and only one medical discipline (intensivist), however, we deliberately started with a French survey because of the very different organizations of ICU exists in Europe.…”
Section: Discussionmentioning
confidence: 97%
“…What influences an individual's ability to cope are primarily the subjective evaluation that the subject makes of it, that is, how he or she perceives the situation. 18 Thus, the effect of perceived stress on the health of professionals is more significant than objective measures of events. Perceived stress has also been shown in many studies to be more predictive of the individual's subsequent health status than actual stress.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of experience assessment tools have been developed [21][22][23], among which the ICEQ has been widely used in UK, US, Australia and other countries, but China still focuses on qualitative research in related elds [24][25], and lacks scienti c assessment tools to quantify ICU patient experience. ICEQ was compiled by Rattray et al [21] based on The Intensive Care Unit Environmental Stressor Scale (ICUESS) and The Intensive Care Unit Memory Tool (ICUMT) and combined with extensive previous literature research and qualitative research [26][27].…”
mentioning
confidence: 99%
“…Health crises such as the current COVID-19 pandemic, are particularly traumatic for HCWs and can severely and durably affect their mental health (Laurent, Fournier, Lheureux, Louis, et al, 2021; Laurent, Fournier, Lheureux, Martin Delgado, et al, 2021 ). Particular attention should therefore be paid to the potential traumatic effects of the pandemic on ICU HCWs, to better understand how they cope with the situation, and what coping mechanisms they used.…”
mentioning
confidence: 99%